Arnold's problems - Arnold Vladimir I (Berlin Springer-Verlag, 2004)
Arnold's Problems contains mathematical problems which have been brought up by Vladimir Arnold in his famous seminar at Moscow State University over several decades. In addition, there are problems published in his numerous papers and books. The second p
Keywords: Mathematics